2017
DOI: 10.1007/978-3-319-62105-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Idea-Caution Before Exploitation: The Use of Cybersecurity Domain Knowledge to Educate Software Engineers Against Software Vulnerabilities

Abstract: The transfer of cybersecurity domain knowledge from security experts ('Ethical Hackers') to software engineers is discussed in terms of desirability and feasibility. Possible mechanisms for the transfer are critically examined. Software engineering methodologies do not make use of security domain knowledge in its form of vulnerability databases (e.g. CWE, CVE, Exploit DB), which are therefore not appropriate for this purpose. An approach based upon the improved use of pattern languages that encompasses securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…This observation suggests that the specific refactorings employed in the analyzed projects were not related to the reduction of the identified vulnerabilities. For instance, the study by Nafees et al [66] revealed that Extract Method refactoring can address Cross-Site Scripting (XSS) vulnerabilities, however, this vulnerability was not among the identified vulnerabilities in the current study.…”
Section: ) Effects Of Refactorings On Vulnerabilitiescontrasting
confidence: 57%
See 1 more Smart Citation
“…This observation suggests that the specific refactorings employed in the analyzed projects were not related to the reduction of the identified vulnerabilities. For instance, the study by Nafees et al [66] revealed that Extract Method refactoring can address Cross-Site Scripting (XSS) vulnerabilities, however, this vulnerability was not among the identified vulnerabilities in the current study.…”
Section: ) Effects Of Refactorings On Vulnerabilitiescontrasting
confidence: 57%
“…The premise could be the performed refactorings did not suffice to remove the identified vulnerabilities. However, we note that refactoring may have a positive impact on vulnerabilities as the study by Nafees et al [66] revealed that Extract Method refactorings can address Cross-Site Scripting (XSS) vulnerabilities. Another similar observation by Shaw et al [74] documented that Extract Method and Move Method refactorings can address overflow vulnerabilities.…”
Section: ) Impact Of Refactorings On Vulnerabilitiesmentioning
confidence: 91%
“…Existing research has noted a gap in communication and security knowledge between developers and security experts (sometimes referred to as auditors) [110,111,165]. Some teams employ a developer who is interested in, or knowledgeable about, security to act as a liaison between the development team and security experts [165].…”
Section: Developers' Abilities and Expertisementioning
confidence: 99%
“…Given that security is not the developer's primary objective, as evidenced by our data and previous work [13,71,178], it is unrealistic to expect that developers will be able to remain current on such issues on top of their regular tasks. In addition, security information is often presented in a manner that is unusable to developers [110,111]. Thus, collaborating with those having high security expertise gives developers a chance to stay updated on security issues, and it could also lead to improving performance and motivation towards software security, as will be discussed later in this chapter.…”
Section: Collaborating In the Workplace ($ B )mentioning
confidence: 99%